Do All Jazz Musicians Wear Berets? - Rowan, Brent (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Brent Rowan reflects on his relationship with Ajay Heble, recalling the many ways their lives have crossed paths in Guelph.